A survey of multicasting protocols for broadcast-and-select single-hop networks. - Hamad, A.M.
Multicast communication in single-hop broadcast-and-select wavelength-division multiplexing networks has received considerable attention from researchers. This article presents a comprehensive survey of the multicast scheduling techniques in this environment. It considers different challenges that are faced in the design of the multicasting techniques and presents a classification of such schemes. A survey of specific techniques is then presented and a comparison is drawn between such techniques
Keywords: QoS; WDM networks; Broadcast-and-select networks; Local lightwave networks; Multicasting protocols; Passive star coupler based networks; Quality of service; Scheduling techniques; Single-hop networks; Wavelength-division multiplexing networks